E-079 Angiographic Anatomical Features for Transbrachial Carotid Cannulation of a Balloon-Guide Catheter. (29th July 2016) - Mori, T; Kasakura, S; Iwata, T; Tanno, Y; Yoshioka, K
Abstract : Background and purpose: Transfemoral approach has been a common technique for advancing a balloon-guide catheter (BGC) for emergency clots removal therapy in acute stroke patients. When aortic or peripheral arterial conditions limit transfemoral access, transbrachial approach is attempted as the alternative. The purpose of our study was to investigate anatomical features of the aortic arch (AA) for transbrachial carotid cannulation (TCC) of a BGC. Patients and methods: Included were patients who underwent endovascular reperfusion therapy with transbrachial BGC between Jan 2014 and Jun 2015. Evaluated were successful cannulation of the BGC and anatomical features of the aortic arch. Results: Fourteen patients were analyzed. TCC was successful in 10 (71%) of 14 lesions: 6 of 7 right carotid artery (CA) lesions and 4 of 7 CA lesions. Two left CA lesions of a bovine type AA were transbrachially cannulated, whereas only two of five left CA lesions of a non-bovine AA were cannulated and their angle (BC-ltCA) between the brachiocephalic artery and the left CA was 20 degree or more. However, three lesions with BC-ltCA angle of less than 20 degree were not cannulated. Six right CA lesions with the angle (SA-rtCA) between the right subclavian artery and the right CA of 30 degree or more were cannulated; however one lesion with SA-rtCA angle of less than 30 degree was not. Conclusion: A BGC can be transbrachially cannulated to the CA in patients with the left CA of a bovine AA, the left CA of a non-bovine AA with the BC-ltCA angle of 20 degree or more or the right CA with the SA-rtCA angle of 30 degree or more. Disclosures: T. Mori: None. S. Kasakura: None. T. Iwata: None. Y. Tanno: None. K. Yoshioka: None.